(untitled) (Journal of Laboratory Animal Science, 2022)
Use of laboratory animals is unavoidable in cancer research throughout the world. It would have been impossible to reconstruct the events that occur in human patients with cancers without use of appropriate animal models. Based on the type of cancer research, various models ranging from normal mice/ rats, GEMM, specialised and super specialised animal models are a choice. Use of more specialised and humanized mice models is advantageous due to higher percentage of tumor acceptance and metastasis rate. However, maintenance of such animals need improved housing and environmental conditions in addition to high quality food/water and trained manpower to maintain these animals. If all these facilities are available, it is not difficult to breed/maintain quality animals for the cancer research with reproducible and meaningful results